2018
DOI: 10.1016/j.ctrv.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel urinary biomarkers for the detection of bladder cancer: A systematic review

Abstract: This comprehensive systematic review provides an update on urinary biomarkers of different 'omic' class and highlights promising biomarkers. Few biomarkers achieve a high sensitivity and negative predictive value. Such biomarkers will require external validation in a prospective observational setting before adoption in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 96 publications
(147 reference statements)
2
62
1
Order By: Relevance
“…A direct comparison of the performance of our markers to those previously reported is difficult due to the vast heterogeneity of the different studies regarding molecular levels, tumor subtypes, tumor history, different statistical approaches, sample size, type of controls and the way the results are reported. At a specificity of ≥95%, only few studies have reported biomarker sensitivities higher than ours . However, several of these markers identify high grade or muscle‐invasive UCa only, whereas our markers identify UCa across all stages and grades.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A direct comparison of the performance of our markers to those previously reported is difficult due to the vast heterogeneity of the different studies regarding molecular levels, tumor subtypes, tumor history, different statistical approaches, sample size, type of controls and the way the results are reported. At a specificity of ≥95%, only few studies have reported biomarker sensitivities higher than ours . However, several of these markers identify high grade or muscle‐invasive UCa only, whereas our markers identify UCa across all stages and grades.…”
Section: Discussioncontrasting
confidence: 53%
“…At a specificity of ≥95%, only few studies have reported biomarker sensitivities higher than ours. 41,42 However, several of these markers identify high grade or muscle-invasive UCa only, whereas our markers identify UCa across all stages and grades. In addition, several of these markers and their diagnostic performances were tested in smaller collectives of UCa patients only.…”
Section: Discussionmentioning
confidence: 80%
“…It is less biologically complex than plasma; however, urinary proteins still exhibit a large dynamic range, with high‐abundant proteins such as uromodulin often masking those with a lower concentration . To combat this, researchers have turned to urinary EVs for the enrichment of disease biomarkers, particularly for diseases of the urogenital system such as bladder cancer, which is hampered by low sensitivity for minimal residual disease testing . One novel study by Smalley and co‐workers investigated the impact of hematuria (blood in the urine, a common symptom of bladder cancer) on EV proteomic profiles by spiking blood from healthy control subjects into urine before HPLC–MS/MS analysis .…”
Section: Urinementioning
confidence: 99%
“…Commercially available tests are licensed only as companion tests as they do not have the required diagnostic performance to replace cystoscopy (sensitivities of 57–82%) . Novel urinary biomarkers have reported high sensitivities but often lack robust prospective validation . Regardless of the performance of current or future urinary‐based biomarkers, it is essential to understand patient perception and willingness to forgo cystoscopy for non‐invasive testing.…”
Section: Introductionmentioning
confidence: 99%